2018
DOI: 10.1080/13803611.2018.1550841
|View full text |Cite
|
Sign up to set email alerts
|

Teacher expectation effects on need-supportive teaching, student motivation, and engagement: a self-determination perspective

Abstract: Previous research has shown that teachers differentiate their behaviour based on their expectations of students. Selfdetermination theory (SDT) makes explicit how teacher behaviour relates to students' motivation and engagement, namely, via needsupportive teaching. In the present study, we combined both research traditions and examined associations of teacher expectations with need-supportive teaching and thereby students' motivation and engagement.Two-hundred-and-seventy-six secondary school students and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 81 publications
(147 reference statements)
3
32
0
Order By: Relevance
“…Studies from the tradition of teacher expectancy research suggest that teachers differentiate their teaching behaviours based on their perceptions of their students’ abilities, motivation, and background characteristics (Jussim & Harber, ; Urhahne, ). This may also apply to differentiation in need support (Hornstra et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from the tradition of teacher expectancy research suggest that teachers differentiate their teaching behaviours based on their perceptions of their students’ abilities, motivation, and background characteristics (Jussim & Harber, ; Urhahne, ). This may also apply to differentiation in need support (Hornstra et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In a small‐scale interview study, teachers indicated that they differentiate in autonomy support and structure based on their perceptions of their students’ ability, background, and motivation (Hornstra, Mansfield, Van der Veen, Peetsma, & Volman, ). In addition, several studies on teacher expectancies have shown that teachers differentiate their teaching behaviours towards individual students based on their expectancies of those students, which in turn affects student motivation (Babad, ; Harris & Rosenthal, ; Hornstra, Stroet, Van Eijden, Goudsblom, & Roskamp, ; Jussim, Eccles, & Madon, ; Urhahne, ).…”
Section: Student Motivationmentioning
confidence: 99%
“…Examples of which are: the lesson subject; students' behaviours (Matos et al 2018;Van den Berghe et al 2016); heavy workloads; feeling pressured (Pelletier, Seguin-Levesque, and Legault 2002;Pelletier and Sharp 2009;Ryan and Deci 2016); and negative perceptions of students' abilities or motivation (Hornstra et al 2015). In other words, teachers' adoption of motivating and demotivating teaching behaviours may differ from lesson to lesson (Hornstra et al 2018;Krijgsman et al 2019;Reeve 2016;Van den Berghe et al 2013). Moreover, there might be specific patterns during lessons of teachers' and students' behaviours that can be identified to understand how the interplay between teacher behaviour and student engagement develops within the course of lessons.…”
Section: Fostering Student Engagement With (De)motivating Teaching Bementioning
confidence: 99%
“…It is also common for past studies to conceptualise motivation or engagement as a unidimensional or bidimensional construct; e.g. perceived reading competence, intrinsic value, and classroom engagement (Whitney and Bergin, 2018); intrinsic motivation, extrinsic motivation, and behavioural engagement (Hornstra et al, 2018); and mastery approach goal orientation, performance approach goal orientation, and academic engagement (Mooney et al 2016).…”
Section: Introductionmentioning
confidence: 99%